2004
DOI: 10.1002/path.1690
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell tryptase may modulate endothelial cell phenotype in healing myocardial infarcts

Abstract: Mast cells and macrophages infiltrate healing myocardial infarcts and may play an important role in regulating fibrous tissue deposition and extracellular matrix remodelling. This study examined the time-course of macrophage and mast cell accumulation in healing infarcts and studied the histological characteristics and protease expression profile of mast cells in a canine model of experimental infarction. Although macrophages were more numerous than mast cells in infarct granulation tissue, macrophage density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 51 publications
1
67
0
2
Order By: Relevance
“…COX-2 in turn is responsible for the enhanced synthesis of 15-deoxy 12,14 prostaglandin J 2 (15-d-PGJ 2 ) among other prostaglandins (i.e. PGI and PGE) (Somasundaram et al 2005;Frungieri et al 2005;Levi-Schaffer and Piliponsky 2003;Gailit et al 2001). It is the PGJ 2 arachidonic acid derived molecule that has been shown to act in the kidney, lung, and vasculature as an endogenous ligand activating PPARγ leading to fibroblast proliferation, collagen deposition, and cytokine production ( Frungieri et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COX-2 in turn is responsible for the enhanced synthesis of 15-deoxy 12,14 prostaglandin J 2 (15-d-PGJ 2 ) among other prostaglandins (i.e. PGI and PGE) (Somasundaram et al 2005;Frungieri et al 2005;Levi-Schaffer and Piliponsky 2003;Gailit et al 2001). It is the PGJ 2 arachidonic acid derived molecule that has been shown to act in the kidney, lung, and vasculature as an endogenous ligand activating PPARγ leading to fibroblast proliferation, collagen deposition, and cytokine production ( Frungieri et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that tryptase, one of the more abundant enzymes contained within mast cells, has modulatory effects on the phenotype of neighboring cells including fibroblasts in the kidney, testis, and lung (Somasundaram et al 2005;Frungieri et al 2005;Skrabal et al 2004;de Almeida et al 2002;Levi-Schaffer and Piliponsky 2003;Gailit et al 2001). Tryptase is a ligand for the protease activated receptor-2 (PAR-2) isoform of the protease ligand class of surface receptors (for review see Steinberg 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Mast cell-derived histamine may critically affect leukocyteendothelial interactions by increasing endothelial P-selectin expression and by facilitating recruitment of rolling leukocytes [222]. Tryptase, the most abundant protease found in mast cell granules stimulates granulocyte recruitment [223], and upregulates cytokine and chemokine synthesis [224], [225]. Mast cell-derived cytokines, such as TNF-α may trigger the cytokine cascade in the infarct, regulating adhesion molecule expression and leukocyte recruitment.…”
Section: The Mast Cellsmentioning
confidence: 99%
“…Proinflamatuar ve vazoaktif mediyatörler, sitokinler ve farkl› enzimler (triptaz, kimaz) sentez edebilen bu hücreler, miyokard infarktüsü sonras› bafllayan inflamatuar süreçde ve skar oluflumunda önemli rol oynarlar. ‹nfarkt alan›n› infiltre eden makrofajlar, lenfositler ve mast hücreleri, proteazlar, sitokinler ve büyüme faktörleri salarak iyileflme sü-recini düzenlerler (2). Mast hücrelerinin inflamatuar infiltrasyon alanlar›ndan ziyade fibrozis alanlar›nda görül-mesi bu hücrelerin fibröz doku birikiminin regülasyo-nunda rol oynad›klar›n› düflündürmektedir (3).…”
Section: öZet Summary G‹r‹fiunclassified
“…Bu deneyde mast hücre say›s› art›fl› ilk olarak reperfüzyondan 72 saat sonra saptanm›fl, 5-7. günlerde fibrotik alanlarda çevre miyokarda göre mast hücre yo¤unlu¤unun belirgin flekilde yüksek oldu¤u görülmüfltür (9). Bir baflka deneysel çal›fl-mada mast hücre say›s›n›n infarkt alan›nda 4. haftaya kadar yüksekli¤ini korudu¤u gösterilmifltir (2). Olgular›-m›zda, literatürle uyumlu olarak, infarktüs sonras› mast hücre say›s›nda en belirgin art›fl 72 saatten sonra izlenmifltir.…”
Section: Tartifimaunclassified